PENINGKATAN PENGUASAAN MUFRADAT MELALUI METODE TAKE AND GIVE DI MTS NEGERI 1 PATI JAWA TENGAH - Lailatun Ni'mah; Noviya Ekasanti; Hijriyatun Hijriyatun; Laily Fitriani (IAIN Batusangkar, Indonesia, 2021)
This study aims to determine how the application of Take and Give (TG) method in learning Arabic could increase students’ vocabulary mastery at MTs Negeri 1 Pati. This was Classroom Action Research (CAR) with two cycles, each of which includes 3 stages, namely 1) planning, 2) implementing and observation, and 3) reflection. Data collection techniques were tests and non-tests. While the research instruments were pre-test items, post-test items and observation sheets. Data were analyzed using comparative descriptive technique by comparing the learning outcomes of pre-cycle, cycle I and cycle II. As a result, Take and Give method could be used as an alternative teaching method to learn mufradat (vocabulary). The students’ learning outcome increased significantly from the initial conditions (pre-cycle) with 21.05% KKM completeness, then increased about 47.37% in cycle I and increased again to 92.11% in cycle II. This meets the indicators of success that at least 75% of all students achieve learning mastery.